2012
DOI: 10.1007/978-94-007-4470-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: Modesto, Fabiana de Ávila. Evaluation of leachate characteristics from landfills in the state of Minas Gerais and analysis of natural wetlands as an alternative for post-treatment. 2021. 127 f. Dissertação (Mestrado Profissional em Rede

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…On a spatial basis, lithological degeneration is the dominant factor in determining the total concentration of heavy metals in world soils. Sediments derived from formations composed of black shales, coals, limestones, ultramafic rocks and sedimentary ironstones are regularly enriched in several heavy metals, although content can vary (Alloway, 2013; Table 1). During weathering, these deposits undergo dissolution and oxidation, and metals are dispersed in regional soils, transported long distances via Aeolian or fluvial transport and/or leached into groundwater (Alloway, 2013;Sweet et al, 1989;Roen, 1984;Tuttle et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…On a spatial basis, lithological degeneration is the dominant factor in determining the total concentration of heavy metals in world soils. Sediments derived from formations composed of black shales, coals, limestones, ultramafic rocks and sedimentary ironstones are regularly enriched in several heavy metals, although content can vary (Alloway, 2013; Table 1). During weathering, these deposits undergo dissolution and oxidation, and metals are dispersed in regional soils, transported long distances via Aeolian or fluvial transport and/or leached into groundwater (Alloway, 2013;Sweet et al, 1989;Roen, 1984;Tuttle et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The pathways through which trace elements enter aquatic systems are diverse. Natural non-point sources like weathering of local geology and deposition of volcanic fallout provide significant inputs of trace metals via runoff or atmospheric deposition (Alloway, 2013). On a spatial basis, lithological degeneration is the dominant factor in determining the total concentration of heavy metals in world soils.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gomah (2016) found that the using of some organic (Charcoal) and inorganic (Silica gel, Cement Bypass and Rock phosphate) materials reduced the DTPA extractable Cd, Ni and Pb from 0.895, 12.097 and 26.02 mgkg -1 in the control treatment to 0.376, 3.13 and 9.06 mg kg -1 , respectively. Cadmium is evidently found in soils at concentrations 0.1 -1 mg/kg (Alloway, 2013). Alternatively, Aydenalp and Gresser (2003) determined that the total Cd level in soils on calcareous material (marl materials) ranged from 0.23 to 0.51 mg/kg in Turkey and DTPA extractable Cd varied from 0.04 to 0.08 mg/kg.…”
Section: Introductionmentioning
confidence: 99%